Past, Present, and Future of DNA Typing for Analyzing Human and Non-Human Forensic Samples - Jordan, Deidra; Mills, DeEtta (Frontiers in Ecology and Evolution, 2021)
Forensic DNA analysis has vastly evolved since the first forensic samples were evaluated by Restriction Fragment Length Polymorphism (RFLP). Methodologies advanced from gel electrophoresis techniques to capillary electrophoresis and now to Next Generation Sequencing (NGS). Capillary electrophoresis was and still is the standard method used in forensic analysis. However, dependent upon the information needed, there are several different techniques that can be used to type a DNA fragment. Short tandem repeat (STR) fragment analysis, Sanger Sequencing, SNapShot, and Capillary Electrophoresis-Single Strand Conformation Polymorphism (CE-SSCP) are a few of the techniques that have been used for the genetic analysis of DNA samples. NGS is the newest and most revolutionary technology and has the potential to be the next standard for genetic analysis. This review briefly encompasses many of the techniques and applications that have been utilized for the analysis of human and nonhuman DNA samples.